Studi Deskriptif Kenakalan Remaja pada Siswa SMAN X Lengayang di Pesisir Selatan - Yuliandri Yuliandri; Mario Pratama (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
The purpose of the study was to determine the description of juvenile delinquency behavior that occurs in students. The study used a descriptive research method in which the author tried to reveal and describe how Juvenile Delinquency in Students of SMAN X Lengayang in Pesisir Selatan. Descriptive research is one type of research that aims to describe systematically, factually, and accurately about the facts and characteristics of a particular population. From the tests that have been carried out, the results obtained are that the level of juvenile delinquency is included in the moderate category. In the gender category, 27 male students have a moderate level of delinquency and 36 female students have a moderate level of delinquency. As for the class category, class 10 has 22 people, class XI 17 people and class XII 24 people with a moderate level of delinquency. The highest level of delinquency is in class XII, this is due to the feeling of being the most senior in school.